2009
DOI: 10.4070/kcj.2009.39.10.418
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Positive Predictive Value of Poor R-Wave Progression and Impact of the Cardiothoracic Ratio

Abstract: Background and ObjectivesPoor R-wave progression (PRWP) is a common electrocardiographic diagnosis. However, the diagnostic usefulness of PRWP for coronary artery disease (CAD) and the plausible explanation for subjects with normal heart function are unclear.Subjects and MethodsWe included 20,739 subjects who had routine medical examinations and applied the commonly used criteria (R-waves in V3 or V4 ≤2 mm) and the Marquette criteria in the current study. Subjects with PRWP by the Marquette criteria, but with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…However, PRWP incidence is reported in some studies as listed in Table 3. A study from the National Cancer Center of Korea reported a lower prevalence of PRWP ranging between 0.5% to 1.8%, depending upon the two criteria [21]. PRWP had been reported to be in the range of 15%-42% based upon different criteria [22].…”
Section: Discussionmentioning
confidence: 99%
“…However, PRWP incidence is reported in some studies as listed in Table 3. A study from the National Cancer Center of Korea reported a lower prevalence of PRWP ranging between 0.5% to 1.8%, depending upon the two criteria [21]. PRWP had been reported to be in the range of 15%-42% based upon different criteria [22].…”
Section: Discussionmentioning
confidence: 99%
“…S wave of greater duration than R wave or greater than 40 ms in leads I and V6. Normal R peak time in leads V5 and V6 but greater than 50 ms in lead V1 [38] Poor R wave progression (PRWP) R-wave in V3 or V4 ≤2 mm [39] Left atrial enlargement (LAE) any one of the following: 1) P wave in any lead > 0.11s, 2) Notched P wave with interpeak duration > 0.04s (P mitrale), 3) P wave axis < 30°, 4) Area of negative P terminal force in lead V1 (NPTF-V1) > 0.04s•mm, or 5) Positive P terminal force in aVL (PPTF-aVL) > 0.5 mm [40] left ventricular hypertrophy (LVH) Sokolow-Lyon voltage criteria: the amplitude of the S wave in lead V1 was added to the largest amplitude of the R wave in either lead V5 or V6, with a value greater than or equal to 35 mm meeting criteria for LVH [41] Right atrial enlargement (RAE) Any one of the following: 1) P wave in inferior leads II, III, aVF > 2.5 mm or 2) Positive P wave in V1 > 1.5 mm [40] Right ventricular hypertrophy (RVH)…”
Section: Availability Of Data and Materialmentioning
confidence: 99%